Nitrogen and Phosphorus Fertilization of Irrigated Grain Sorghum - A. Schlegel; H. D. Bond (Kansas Agricultural Experiment Station Research Reports, 2015)
(Abstract only. Link to:http://newprairiepress.org/kaesrr/vol1/iss3/6/) Article is nearly identical to Long-Term Nitrogen and Phosphorus Fertilization of Irrigated Grain Sorghum, previously published in Kansas Fertilizer Research 2015, included in this PDF. Long-term research shows that phosphorus (P) and nitrogen (N) fertilizer must be applied to optimize production of irrigated grain sorghum in western Kansas. In 2014, N applied alone increased yields 49 bu/a, whereas N and P applied together increased yields up to 81 bu/a. Averaged across the past 10 years, N and P fertilization increased sorghum yields up to 73 bu/a. Application of 40 lb/a N (with P) was sufficient to produce more than 80% of maximum yield in 2014, which almost equals the 10-year average. Application of potassium (K) has had no effect on sorghum yield throughout the study period.
Keywords: soil fertility; irrigation; grain sorghum; nitrogen fertilization; phosphorus fertilization